Heteroleptic Ruthenium Sensitizers with Hydrophobic Fused‐Thiophenes for Use in Efficient Dye‐Sensitized Solar Cells. Issue 8 (22nd February 2016) - Lu, Zong‐Zhan; Peng, Jia‐De; Wu, An‐Kai; Lin, Chun‐Han; Wu, Chun‐Guey; Ho, Kuo‐Chuan; Lin, Ying‐Chih; Lu, Kuang‐Lieh
Abstract: Two fused‐thiophene‐containing ruthenium sensitizers, [Ru(Hdcbpy)(ottip)(NCS)2 ] – · 0.5[H] + · 0.5[N(C4 H9 )4 ] + [Z1, H2 dcbpy = 4, 4′‐dicarboxy‐2, 2′‐bipyridine, ottip = 2‐(5‐octylthieno[3, 2‐ b ]thiophen‐2‐yl)‐1 H ‐imidazo[4, 5‐ f ][1, 10]phenanthroline] and [Ru(Hdcbpy)(odttip)(NCS)2 ] – · 0.5[H] + · 0.5[N(C4 H9 )4 ] + {Z2, odttip = 2‐[6‐octyldithieno(3, 2‐ b :2′, 3′)thiophen‐2‐yl]‐1 H ‐imidazo[4, 5‐ f ][1, 10]phenanthroline}, were designed for use in dye‐sensitized solar cell (DSSC) applications. The fused‐thiophene‐basedZ1 andZ2 have stronger light‐harvesting capabilities compared with a non‐fused‐thiophene analog, [Ru(Hdcbpy)(otip)(NCS)2 ] – · 0.5[H] + · 0.5[N(C4 H9 )4 ] + [JF‐2t, otip = 2‐(5‐octylthiophen‐2‐yl)‐1 H ‐imidazo[4, 5‐ f ][1, 10]phenanthroline], and a standard N3 dye. The power‐conversion efficiency of theZ1 ‐ andZ2 ‐sensitized solar cells were superior (8.70 % and 8.15 %) toJF‐2t ‐ and N3‐sensitized solar cells (7.85 and 7.40 %, respectively) under standard AM1.5G full sunlight irradiation. The photovoltaic performance ofZ1 was better thanZ2, primarily owing to the fact thatZ1 ‐based cells have a higher level of dye loading and less charge recombination, as seen from the electrochemical impedance spectroscopy data. This study not only demonstrates the excellent power‐conversion efficiency of new fused‐thiophene ruthenium sensitizers, but also points to the promise that fused‐thiophene antennas might be a useful molecule in the engineering of ruthenium dyes for DSSCs. Abstract : Optimization of the power‐conversion efficiency in ruthenium sensitizers containing fused‐thiophene antennas was achieved. This result clearly confirms that fused‐thiophenes can be used as a superior antenna in the design of ruthenium sensitizers for greater dye‐sensitized solar cells (DSSC) performance.